A correlational study of biomechanical variables and aesthetic artistry in grand pas de chat - Jung, J.-E.; Lee, K.-I. (Korean Journal of Sport Biomechanics, 2016)
Objective: The objective of this study is to present a scientific basis for ballet dancer training methods by analyzing the relationships between subjective assessment of the ballet movement 'Grand pas de chat' and kinematic and electromyographic factors. Method: The subjects were 14 professional dancers with 15 years of experience on average. Four cameras and a wireless electromyogram were used to examine kinematic factors, and the filmed videos were analyzed by 3 experts for subjective assessment. Results: Although no differences in kinematic factors were found between the excellent dancer group and the non-excellent dancer group divided based on the experts' assessment, some difference was found in electromyographic factors, especially in relation to the gastrocnemius muscle, rectus femoris muscle, and erector spinae muscle. A relationship between subjective assessment and kinematic and electromyographic factors was found, and factors such as right-side rectus femoris activation, time required, left-side gastrocnemius activation, and front-back displacement affected subjective assessment. Conclusion: This study showed a relationship between subjective assessment and kinematic and electromyographic factors. To receive higher scores in subjective assessment, it is necessary to extend the hang time by using the lower limb muscles. The findings of this study also indicate the necessity of weight training in order to improve dancing techniques.